Microbial Degradation of High Molecular Weight Polycyclic Aromatic Hydrocarbons with Emphasis on Pyrene. (15th March 2019) - Gupta, Gauri; Kumar, Vipin; Pal, A. K.
ABSTRACT: Biodegradation of polycyclic aromatic hydrocarbons (PAHs) is a major concern in the environment due to their toxic nature and ubiquitous occurrence. PAHs remain sorbed to soil organics and interact with non-aqueous phases and therefore, become less available for degradation. Several microorganisms like bacteria, fungi, and algae have the capability to degrade soil-sorbed PAHs using different metabolic pathways. The focus of this review is microbial degradation of high molecular weight PAH pyrene by pure and mixed culture, including biological aspects of biosurfactants produced during the process for increasing the bioavailability of soil-sorbed or non-aqueous phase pyrene. High molecular weight PAHs are generally recalcitrant to microbial attack, although some bacteria, fungi, and algae are capable of transforming these compounds by using them as the sole source of carbon and energy. Also, the use of microbial consortium has been found to be more efficient and better from an economic point of view for degradation due to synergistic interactions among microbial species. The review also explains the role of catabolic genes involved in the degradation of pyrene.